The Foreign Policy Implications of the Belt and Road Initiative in the Mekong Region : Comparative Case Studies of Laos and Cambodia - Starilova, Anna; Garlick, Jeremy; Hompot, Sebestyén; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the foreign policy responses of Laos and Cambodia to China's Belt and Road Initiative (BRI), analyzing how small states navigate asymmetric relations amid expanding Chinese influence in Southeast Asia. Using a comparative case study approach, the research applies the frameworks of Neoclassical Realism and Foreign Policy Analysis to examine the complex interplay between systemic pressures and domestic variables. The analysis demonstrates that Laos conceptualizes the BRI as a means to national development and regional integration, emphasizing its transformation from a 'landlocked' to a 'land-linked' state. In contrast, Cambodia leverages the Initiative primarily as a tool for consolidating regime authority, particularly in the context of strained relations with Western actors. The comparative findings highlight the importance of internal governance structures and elite preferences in shaping foreign policy orientations. As a result, the study offers insight into how domestic political factors shape the foreign policy behavior of economically dependent states in response to China's strategic engagement.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses